Acute pancreatitis associated with scoliosis surgery: Could opioids be a determinant factor in its development? (Indian Journal of Case Reports, 2024)
Various medical complications can occur after spinal surgery in the pediatric population. Current surgical techniques have allowed a greater degree of scoliosis correction, but at the same time, unusual complications have been described that seem to be associated and have a multifactorial etiology. We present a case series of three pediatric patients who underwent scoliosis correction surgery with continuous use of full-dose opioids, and during hospitalization and post-operative surveillance developed acute pancreatitis. The association between prolonged exposure to high-dose opioids and the onset of pancreatitis in the context of major surgery suggests a potential relationship that warrants further study.